Accurate screening for drought tolerance in lentils (Lens culinaris Medik) - Andrea Fernandez-Gutierrez; Alvaro F. Rodriguez-Torres; Juan J. Gutierrez-Gonzalez (Plant Stress)
Lentils (Lens sp.) are among the most important legumes worldwide, but drought periods cause serious yield losses. Although lentils are considered moderately drought tolerant, differences among accessions have been found. Various protocols have been tested, with no evidence on which one provides the most accurate evaluation of stress, or if they are genotype dependent. We adopted a slow-progressing water withholding protocol in a greenhouse to mimic long drought periods in field conditions and used it to evaluate nine accessions (cultivated and wild). A number of morphological and physiological parameters were quantified: relative water content (RWC), xylem water potential (Ψx), photosynthesis assimilation rate (A), stomatal conductance (gs), transpiration rate (Tr), root biomass and several yield traits. The objectives were to: (i) gauge the response of diverse lentil accessions to drought stress; (ii) judge which drought-tolerance strategy is followed by each accession; and (iii) establish the most general, reliable, and consistent parameters for drought evaluation in lentils. Results suggest the coexistence of different drought tolerance mechanisms within the lentil species, as previously seen in other legume crops. While some accessions were able to sustain water status relying on enhanced root growth, following a water spender strategy; others sustained water status by efficient stomatal closure, following a water saver strategy. Concerning protocols for evaluating drought tolerance, RWC appears to be the most accurate parameter to assess the stress caused by drought, regardless of the type of response activated. We also identified two highly tolerant accessions able not only to keep a high RWC under drought but also to maintain photosynthesis rates.